Opportune period for screening wheat germ plasm against powdery mildew in Punjab - INDU SHARMA; KARAM CHAND, UPASANA RANI*, G.D. MUNSHI (Indian Phytopathology, 2008)
Powdery mildew is an important foliar disease of wheat. Wheat variety PBW 343 that is being widely grown in the northwestern plain zone has recently shown susceptibility to this disease. The crop is sown on variable dates by farmers of the state. To evaluate the sowing time congenial for powdery mildew, homozygous breeding lines from advanced yield trials were sown on different dates and evaluated against powdery mildew based on 0-9 scale at PAU, Ludhiana. Out of 300 lines evaluated, 22 breeding lines showed resistant reaction on all the three dates of sowing. Susceptibility was higher in the late sown crop because during this period availability of inoculum was more, crop growth stage was vulnerable to infection and environmental conditions remained favourable for the disease development.